Analysis academic information system at Muhammadiyah university palembang - Muhammad Andryansyah; Apriansyah (International Journal Cister, 2022)
Academic Information System is a system that is used as a tool to facilitate access, the University of Muhammadiyah Palembang Academic Information System accesses a Study Plan Card, Study Result Card, Transcript, Lecture Schedule Input, Course Input, Student Activity Data Reports. In accessing the overall data, it is only given to the Palembang UM Operator, while for the Faculties it is only given access to the work of each faculty by the respective Faculty Operators, and for students they can only access an Online KRS Input, Online KRS Output, KHS Print, and Transcript of Scores.